2019
DOI: 10.24200/sci.2019.51698.2319
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration response of functionally graded carbon nanotubes double curved shell and panel with piezoelectric layers in a thermal environment

Abstract: This paper presents free vibration of the double-curved shells and panels with piezoelectric layers in a thermal environment. Vibration characteristics of elliptical, spherical, cycloidal, and toro circular shells of revolution are studied in detail. These structures are made of a based carbon nanotubes (CNTs) core and piezoelectric layers at the upper and lower surfaces. It is supposed that temperature changes linearly through the thickness direction. Reissner-Mindlin and the first order shear deformation (FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…They found that an increase in in-homogeneous index of sensor and actuators leads to an increase in natural frequencies. Khorshidi et al [ 17 ] developed the general formulation for dynamic response analysis of the various geometric shells integrated with piezoelectric layers reinforced with carbon nanotubes. The responses were obtained for different geometries such as cycloidal, spherical, elliptical, and toro-circular shell of revolution based on Mindlin plate theory.…”
Section: Introductionmentioning
confidence: 99%
“…They found that an increase in in-homogeneous index of sensor and actuators leads to an increase in natural frequencies. Khorshidi et al [ 17 ] developed the general formulation for dynamic response analysis of the various geometric shells integrated with piezoelectric layers reinforced with carbon nanotubes. The responses were obtained for different geometries such as cycloidal, spherical, elliptical, and toro-circular shell of revolution based on Mindlin plate theory.…”
Section: Introductionmentioning
confidence: 99%
“…For determining the vibration characteristics of composite shells and panels in the presence of nanoparticles, numerical and experimental methods have been employed by many researchers. [35][36][37][38][39][40] Kamarian et al 41 analyzed the vibration characteristics of conical shells based on firstorder shear deformation theory (FSDT) in the presence of agglomerated CNTs using the generalized differential quadrature (GDQ) method. Das et al 42 studied the buckling and vibration of randomly distributed CNT-reinforced composite beams in the presence of thermomechanical loading.…”
Section: Introductionmentioning
confidence: 99%